1978
DOI: 10.1073/pnas.75.8.3953
|View full text |Cite
|
Sign up to set email alerts
|

Murine Ia and human DR antigens: homology of amino-terminal sequences.

Abstract: Murine Ia and human DR antigens were isolated and purified by immunoprecipitation and sodium dodecyl sulfate/polyacrylamide gel electrophoresis with allo-and xenoantisera, respectively. The I-A subregon antigen consists of two chains, designated Aa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…In man, the situation is less clear. Partial NH2-terminal sequences of HLA-DR antigens isolated from B-cell lines show homology only with the I-E/C polypeptides of the mouse and not with I-A products (18,19). Similarly, serological analysis of the cross-reactions of mouse anti-Ia alloantisera on human cells showed a predominant, correlation with L-E/C specificities (20,21).…”
mentioning
confidence: 99%
“…In man, the situation is less clear. Partial NH2-terminal sequences of HLA-DR antigens isolated from B-cell lines show homology only with the I-E/C polypeptides of the mouse and not with I-A products (18,19). Similarly, serological analysis of the cross-reactions of mouse anti-Ia alloantisera on human cells showed a predominant, correlation with L-E/C specificities (20,21).…”
mentioning
confidence: 99%
“…However, serological crossreactivities (33), the presence of two chains (one nearly invariant, the other highly polymorphic), and NH2-terminal sequence homology (34) point to a strict analogy between human DR and mouse IE/C alloantigens. It is therefore possible, as recently demonstrated by Jones et aL (35) for the latter, that the a chains are MHC encoded as well, and their minor differences are the expression of a more limited but real polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…DR antigens are composed of two noncovalently linked chains, apparently [33][34][35] kDal (heavy or a chain) and [26][27][28][29] kDal (light or 13 chain) (12,13). They appear to be equivalent to the mouse Ta antigens, to which a number of functions in the immune response have been assigned (1,14).…”
mentioning
confidence: 99%
“…Recent immunogenetic studies indicate that a common link between the 2 diseases may be the HLADRw4 locus, since the frequency of this allele has been reported to be increased in psoriatic atthritis (34) as well as in rheumatoid arthritis (35,36). Human immune response (Ir) genes appear to be localized near the D locus (37,38). Although Smolen et al (25) have reported that thymidine incorporation responses to denatured type I collagen by cells from patients with RA are not associated with the presence of HLA-DRw4, we have initiated a study to determine whether the capacity to respond immunologically to native type I1…”
Section: Discussionmentioning
confidence: 99%